Geochemistry of Igneous Rocks of Citirem Formation and Its Implications for the Tectonic Setting in Ciletuh – Palabuhanratu UNESCO Global Geopark Area - Hafidhah Nurul Haq; Rosana, Mega Fatimah; Endyana, Cipta; Nugraha, Katon Sena Ajie; Alamsyah, Irpan (UIR PRESS, 2024)
The igneous rocks of the Citirem Formation in the Ciletuh – Palabuhanratu UNESCO Global Geopark area petrographically not only consist of basalt, but also andesite, dacite, and gabbro. The characteristics of basalts Citirem Formation are composed of plagioclase 43% – 58% and olivine, mostly have amygdaloidal and aphanitic textures. Andesites are composed of 45% – 65% plagioclase, absence of olivine, mostly aphanitic and trachytic, some have intergranular textures. Dacite comprises 50% plagioclase, 20% quartz, and the absence of olivine, and aphanitic, intersertal textures. Gabbros are composed of 62% plagioclase, 6% – 12% olivine, with phaneritic texture. Based on the plot of the major elements vs SiO2 diagram, MgO, FeOt (Fe2O3+FeO), CaO, and TiO2 show a negative correlation with SiO2. In comparison, Na2O and K2O show a positive correlation with SiO2. The lithology of igneous rocks of Citirem Formation are basalt, trachybasalt, basaltic trachyandesite, trachyandesite, andesite, dacite and gabbro based on a plot of the Na2O+K2O vs SiO2 diagram for volcanic and plutonic rocks. The origin of magma type can be distinguished based on the plot of K2O vs SiO2 diagrams, the igneous rocks of Citirem Formation are divided into low-K, medium-K, high-K, and shoshonite magma series. Dacite STA 2, andesite STA 7, basaltic andesite STA 8, trachyandesite STA 10 and gabbro STA 14 are calc-alkaline based on triangular diagram Th-Hf-Ta-Zr-Nb. Gabbro STA 17 indicates IAT (island arc tholeiite), trachybasalt STA 19, basalt STA 20 and basaltic trachyandesite STA 27 are E-MORB, WPT (within plate tholeiitic), In contrast, trachybasalt STA 28 is WPA (within plate alkali). Primitive mantle long, NMORB-normalized REE patterns and chondrites-normalized show some rocks have distinctive patterns that have similarities with suprasubduction zone ophiolite rocks, MORB of Mirdita ophiolite, and some show similarities with patterns from OIB and E-MORB.